ANALYSIS OF THE POTENTIAL COMPETITIVENESS OF NATURAL RUBBER EXPORTS IN THE GLOBAL MARKET (COMPARATIVE STUDY IN ITRC COUNTRIES: INDONESIA, THAILAND, AND MALAYSIA) - Hodijah, Siti; Mustika, Candra; Rahmadani, Desy (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2023)
The objectives of this study are 1) to find out how the potential competitiveness of Indonesian, Thailand, and Malaysian natural rubber exports in the global market compares in terms of their comparative advantages 2) to find out how the comparison of the effect of the exchange rate, production, and the international price of natural rabber on the competitiveness of Indonesian, Thailand, and Malaysian natural rubber export in the global market. The method used in this study is a quantitative method with Revealed Comparative Advantage (RCA) and Revealed Symmetric Comparative Advantage (RSCA) analysis tools to analyze the export competitiveness of Indonesian, Thailand, and Malaysian natural rubber based on their comparative advantage, and multiple linear regression with the ordinary least square (OLS) method. 1) The results of this study indicate that for Indonesia the average competitiveness of natural rubber exports is 0.9330, while Thailand is 0.9338, and Malaysia is 0.7763. 2) The results of multiple linear regression show that the exchange rate and production variables have no significant effect on the competitiveness of Indonesian and Thailand natural rubber exports, while the international price variable for natural rubber has a significant effect on the competitiveness of Indonesian and Thailand natural rubber exports. And for Malaysia, it shows that the three variables, the exchange rate, production, and international prices of natural rubber have a significant effect on the competitivenss of Malaysia’s natural rubber exports. Keywords: ITRC country’s natural rubber export competitiveness, Exchange Rates, Production, and International Price of Natural Rubber.